Soluble urokinase plasminogen activator receptor as a marker for use of antidepressants. - Eva Haastrup (Public Library of Science (PLoS), 2014)
Objectives Inflammation is involved in the pathogenesis of depression. A few cross-sectional population-based studies have found that depression is associated with increased levels of inflammatory markers. Soluble urokinase plasminogen activation receptor (suPAR) is known to be a stable marker for inflammation. We investigated the bidirectional association between suPAR levels and use of antidepressants. Methods suPAR level was measured in 9305 blood donors and analysed in relation to 5-years follow-up data on purchase of antidepressants and hospital diagnoses of depression from a nationwide Danish register. Results For men and women without prior use of antidepressants we found a significantly higher risk for incident use of antidepressants with higher suPAR values. For men, the risk of first use of antidepressants increased by 72% from the 1st to the 4th quartile (HR = 1.72, 95% CI: 1.11-2.69). For women, it increased by 108% from the 1st to the 4th quartile (HR = 2.08, 95% CI: 1.45-2.98). Previous use of antidepressants was also significantly associated with higher suPAR levels (p = 0.002). Conclusions High suPAR levels are associated with an increased risk for both previous and future use of antidepressants in healthy men and women. High suPAR are also associated with increased risk for a hospital diagnosis of depression.